Optimization of Financial Management and Management of the Cupu Manik Sedana Waste Bank in Dangin Puri Kaja Village - MARTINI, Ni Putu Riski; PRILIANDANI, Ni Made Intan (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
Waste management is a complex issue faced by various regions in Indonesia, including Bali Province, where organic waste dominates the household waste composition. In response, Dangin Puri Kaja Village established the “Cupu Manik Sedana” waste bank in 2022, aimed at transforming waste into resources of economic value while reducing its environmental impact. Despite this initiative, several challenges hindered its operations: (1) financial records were poorly organized and lacked systematic bookkeeping, (2) human resources had limited skills in management and production, and (3) there was a need for education and training in processing organic waste into Liquid Organic Fertilizer (POC). To address these issues, a community service program was designed to empower the waste bank by strengthening financial literacy, improving human resources, and providing practical training in waste utilization. The methods implemented included participatory mentoring, structured counseling, and hands-on practice. Training in financial literacy introduced partners to basic accounting principles, daily transaction records, and financial reporting using Microsoft Excel and the Sepran cash book application. Human resource development focused on time management, division of labor, and enhancing productivity among group members. Additionally, practical workshops on POC production provided participants with the skills to convert kitchen waste into valuable fertilizer, reinforcing the principles of reduce, reuse, and recycle.